2017
DOI: 10.28945/3887
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Examination of Customers’ Mobile Phone Experience and Awareness of Mobile Banking Services in Mobile Banking in Saudi Arabia

Abstract: Aim/Purpose: This work aims to understand why a disparity between the popularity of smart phones and the limited adoption of m-banking exists. Accordingly, this study investigates factors that affect a person’s decision to adopt m-banking services. Such an investigation seeks to determine if and to what extent customers’ mobile phone experience as well as their awareness of m-banking services influence their intention to use such services? Background: This study developed a conceptual model to determine the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…Our study found that PU, PEOU (Alalwan et al, 2018;Chawla & Joshi, 2020;Hassan et al, 2021;Kumar et al, 2020;Püschel et al, 2010;, CA (Alkhaldi, 2017;Hassan et al, 2021;Mutahar et al, 2018), PR (Gupta et al, 2017;Laukkanen & Kiviniemi, 2010;Mohapatra et al, 2020;Susanto et al, 2020) and PT (Engwanda, 2014;Kumar et al, 2020;Lin, 2011;Shankar et al, 2020;Tarhini et al, 2019) were found to be significant in m-banking adoption.…”
Section: Findings Discussion and Implicationsmentioning
confidence: 53%
“…Our study found that PU, PEOU (Alalwan et al, 2018;Chawla & Joshi, 2020;Hassan et al, 2021;Kumar et al, 2020;Püschel et al, 2010;, CA (Alkhaldi, 2017;Hassan et al, 2021;Mutahar et al, 2018), PR (Gupta et al, 2017;Laukkanen & Kiviniemi, 2010;Mohapatra et al, 2020;Susanto et al, 2020) and PT (Engwanda, 2014;Kumar et al, 2020;Lin, 2011;Shankar et al, 2020;Tarhini et al, 2019) were found to be significant in m-banking adoption.…”
Section: Findings Discussion and Implicationsmentioning
confidence: 53%
“…Aside from the above, the influence of users' individual characteristics on technology acceptance has been theoretically justified and empirically supported to demonstrate that men and women have different concerns over the role of performance expectancy, effort expectancy, and/or social influence in technology adoption (Alkhaldi, 2017;Gefen & Straub, 1997;Hilao & Wichadee, 2017;Terzis & Economides, 2011;Venkatesh et al, 2003). Other studies have suggested a relationship between more advanced age with difficulty in processing information and using software systems (Tarhini, Hone, & Liu, 2014;Venkatesh et al, 2003).…”
Section: Individual Differencesmentioning
confidence: 99%
“…Study (Bhatiasevi, 2015), with the context of the UTAUT model research on the adoption of mobile banking, concluded that performance expectations and behavioral intentions to use mobile banking suggest a positive relationship. The study conducted by (Alkhaldi 2014) stated that effort expectancy significantly affects behavioral intention mobile banking in Saudi Arabia. Following the results of several previous studies, the formulation of the developed hypothesis is:…”
Section: Literature Reviewmentioning
confidence: 99%